Preclinical Assessment of Safety of Maternal Vaccination Against Respiratory Syncytial Virus (RSV) in Cotton Rats - Blanco, Jorge C. G. (Vaccine, 2017)
Maternal immunization directed to control RSV infection in newborns and infants is an appealing vaccination strategy currently under development. In this work we have modeled maternal vaccination against RSV in cotton rats (CR) to answer two fundamental questions on maternal vaccine safety. We tested (i), whether a known, unsafe RSV vaccine (i.e., FI-RSV Lot 100 vaccine) induces vaccine enhanced disease in the presence of passively transferred, RSV maternal immunity, and (ii) whether the same FI-RSV vaccine could induce vaccine enhanced disease in CR litters when used to immunize to their RSV-primed mothers. Our data show that FI-RSV immunization of pups with subsequent RSV infection results in vaccine-enhanced disease independent of whether the pups were born to RSV-seropositive or RSV-seronegative mothers, and that FI-RSV immunization of RSV-seropositive mothers does not present a health risk to either the mother or the infant. Our study also raises a novel concern regarding infant immunization, namely that “safe” RSV vaccines (e.g., live RSV administered intramuscularly) may induce vaccine-enhanced disease in RSV-infected pups born to seropositive mothers. Finally, we describe for the first time a sharp decrease in RSV neutralizing antibody titers in immunized seropositive CR at the time of delivery. This decline may reflect maternal immune suppression, potentially pinpointing a window of increased vulnerability to RSV infection that could be alleviated by effective immunization of expectant mothers.